Flood analysis of Sungai Isap, Kuantan using different rainstorm hours - Mohamad Faizol, Buang (2011)
The purpose of this paper was to analyse flood based on the past event tragedy. Flood is considered the most severe as hazard in Malaysia, due to a wet equatorial climate with heavy rainfall during monsoon season. This study was carried out at Sungai Isap, Kuantan based on different rainstorm hours (2, 3 and 6) for 5, 10, 50, and 100 years of ARI using infoworks RS software. From this analysis, it indicated that Sungai Isap could not withhold the volume of rainfall during the monsoon season. Rainfall patterns and critical areas within the Sungai Isap catchment were also identified. This study could assist in forecasting and preparing for the upcoming flood.